STUDY OF ARACHIDONOYL SPECIFICITY IN TWO ENZYMES OF THE PI-CYCLE - Shulga, Yulia V. (2011)
We identified a conserved pattern of residues L-X((3–4))-R-X((2))-L-X((4))-G, in which -X((n))- represents n residues of any amino acids, in two enzymes acting on polyunsaturated fatty acids, diacylglycerol kinase epsilon (DGKε) and phosphatidylinositol-4-phosphate-5-kinase Iα (PIP5K Iα). DGKε is the only one of the 10 mammalian isoforms of DGK that exhibits arachidonoyl specificity and is the only isoform with the aforementioned motif. Mutations of the essential residues in this motif result in loss of arachidonoyl specificity. Furthermore, DGKα can be converted to an enzyme having this motif by substituting only one residue. When DGKα was mutated so that it gained the motif, the enzyme also gained some specificity for arachidonoyl-containing diacylglycerol. This motif is also present in an isoform of phosphatidylinositol-4-phosphate-5-kinase that we demonstrated had arachidonoyl-specificity for its substrate. Single residue mutations within the identified motif of this isoform result in loss of activity against an arachidonoyl substrate. The importance of acyl chain specificity for the phosphatidic acid activation of phosphatidylinositol-4-phosphate-5-kinase is also shown. We also demonstrate that the acyl chain dependence of this phosphatidic acid activation is dependent on the substrate. This is the first demonstration of a motif that endows specificity for an acyl chain in two studied enzymes, DGKε and PIP5K Iα.